Transformational principal leadership and teacher performance as predictors of primary education quality: a multiple regression study - Eko Rudiyanto; Edi Harapan; Syaiful Eddy (Jurnal Konseling dan Pendidikan, 2026)
This study examined the individual and simultaneous contributions of principals’ transformational leadership and teacher performance in predicting educational quality in public elementary schools. A quantitative cross-sectional correlational design was employed. The population consisted of 88 teachers from seven public elementary schools in Muara Telang District, Banyuasin Regency. A sample of 72 teachers was selected using proportional random sampling based on the Slovin formula with a 5% margin of error. Data were collected using Likert-scale questionnaires. All 30 transformational-leadership items and all 30 teacher-performance items were valid, whereas 29 of 30 educational-quality items were valid. Each scale demonstrated high internal consistency (Cronbach’s alpha = 0.80). Data were analyzed using descriptive statistics, simple linear regression, and multiple linear regression. Transformational leadership significantly predicted educational quality and explained 26.2% of its variance (R = 0.512; R² = 0.262; t = 4.988; p < 0.001). Teacher performance also significantly predicted educational quality and explained 21.7% of its variance (R = 0.466; R² = 0.217; t = 4.407; p < 0.001). Simultaneously, both predictors explained 34.0% of the variance in educational quality (R = 0.583; R² = 0.340; adjusted R² = 0.320; F(2, 69) = 17.737; p < 0.001). The overall model demonstrated a substantial effect size (Cohen’s f² = 0.515) and statistical power exceeding 0.99. The findings indicate that transformational principal leadership and teacher performance are complementary predictors of educational quality. Because the design was cross-sectional and correlational, the results should be interpreted as predictive associations rather than definitive causal relationships.